Analysis of Perceived Quality, Customer Satisfaction, and Customer Experience in Customer Loyalty at the Astra Daihatsu Surabaya workshop - Lilik Indayani; Dwi Salsabila Ulfirin; Muhammad Yani (BIMA Journal (Business, Management, & Accounting Journal), 2026)
Purpose: This study aims to analyze the influence of perceived quality, customer satisfaction, and customer experience on customer loyalty at the Astra Daihatsu Surabaya Workshop. This research is important to identify key factors that can strengthen customer loyalty amid intense competition in the automotive service industry and declining market conditions. Methodology: This research uses a quantitative approach with primary data collected through questionnaires distributed to 100 customers of the Astra Daihatsu Surabaya Workshop using purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS to test validity, reliability, and hypothesis relationships. Results: The results indicate that perceived quality, customer satisfaction, and customer experience have positive and significant effects on customer loyalty. Customer experience shows the strongest influence, followed by perceived quality and customer satisfaction. Findings: The study reveals that customer experience is the most dominant factor in shaping customer loyalty, highlighting the importance of service interactions, comfort, and emotional engagement. Novelty: This research integrates customer experience alongside perceived quality and customer satisfaction as independent variables influencing customer loyalty in the automotive workshop context. Originality: The study positions customer satisfaction as an independent variable and applies the Theory of Planned Behavior to explain customer loyalty behavior. Conclusion: Improving service quality, enhancing customer experience, and maintaining customer satisfaction are crucial strategies for strengthening customer loyalty. Type of Paper: Empirical research article.